2017
DOI: 10.1039/c7an01161j
|View full text |Cite
|
Sign up to set email alerts
|

Development of lithium attachment mass spectrometry – knudsen effusion and chemical ionisation mass spectrometry (KEMS, CIMS)

Abstract: Lithium ion attachment mass spectrometry provides a non-specific, non-fragmenting, sensitive and robust method for the detection of volatile species in the gas phase. The design, manufacture and results of lithium based ion attachment ionisation sources for two different mass spectrometry systems are presented. In this study trace gas analysis is investigated using a modified Chemical Ionization Mass Spectrometer (CIMS) and vapour pressure measurements are made using a modified Knudsen Effusion Mass Spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The importance of this fundamental property is discussed extensively in Bilde et al (2015), and the sensitivity of predicted mass, composition and particle properties to uncertainties in VP vary according to the complexity of the system being studied, both with regards to the number of compounds used in partitioning and additional processes included in any model (Valorso et al, 2011;O'Meara et al, 2014;McVay et al, 2016). Single-component measurements of vapour pressures using instruments such as the Knudsen Effusion Mass Spectrometry (KEMS), following the methodology of Booth et al (2009), have been recently reported (Booth et al, 2012;Bannan et al, 2017) and have been extended to consider vapour pressures in simple multicomponent systems (Booth et al, 2017). Such measurements are ongoing with the KEMS, focusing on atmospherically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this fundamental property is discussed extensively in Bilde et al (2015), and the sensitivity of predicted mass, composition and particle properties to uncertainties in VP vary according to the complexity of the system being studied, both with regards to the number of compounds used in partitioning and additional processes included in any model (Valorso et al, 2011;O'Meara et al, 2014;McVay et al, 2016). Single-component measurements of vapour pressures using instruments such as the Knudsen Effusion Mass Spectrometry (KEMS), following the methodology of Booth et al (2009), have been recently reported (Booth et al, 2012;Bannan et al, 2017) and have been extended to consider vapour pressures in simple multicomponent systems (Booth et al, 2017). Such measurements are ongoing with the KEMS, focusing on atmospherically relevant compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The isomers DBP and DIBP have identical mass numbers. As is the case with the ion attachment mass spectrometry (IA-MS), [2931] the mass separation cannot directly be achieved, with the present system, for the isomers with identical mass numbers such as DBP and DIBP (figure 3). Accordingly, DBP and DIBP were evaluated as one mass spectrum of the same mass number (table 2).…”
Section: Resultsmentioning
confidence: 98%
“…The PEG series has now been employed by new techniques such as, those in Booth et al (Booth et al, 2017) and Bannan et al (Bannan et al, 2019).…”
Section: Knudsen Effusion Mass Spectrometry System (Kems)mentioning
confidence: 99%